Rumenostomy and Flexible Cannula Insertion in Sheep: : Anesthetic and Surgical Technique in Standing Position - Madeira Correa de Moraes, Vivian; Guimarães Santana Freire, Natália; Santiago de Carvalho, Vitor; Machado Sales da Cruz Ferreira, Anna Fernanda; Martins Barbosa, Analívia; Velozo Leal, Paula; Rodrigues de Oliveira, Alice; Gouvêa Teixeira, Luisa (Acta Scientiae Veterinariae, 2025)
Background: The fistulation technique associated with the insertion of a rumen cannula is an important in vivo tool both for biotechnological research in the field of nutrition, as it enables the continuous collection of rumen samples for analysis of digestive processes, and for emergency treatment in ruminant medicine, such as vagal indigestion or for transfaunation. The objective of this study is to report the surgical technique of rumenostomy and the anesthetic protocol used for the placement of a flexible cannula in sheep, in a standing position. Materials, Methods & Results: Six healthy, intact male sheep, 6 months of age and weighing between 23.5 kg and 29 kg, selected for a digestibility study were used. The surgical procedure was performed with the animals in a standing position, manually restrained, under sedation with fentanyl and midazolam, subanesthetic dose of ketamine, and paravertebral anesthetic block with ropivacaine. The rumenostomy surgery was carried out in the center of the left paralumbar fossa in a single step, followed by the insertion of a flexible latex cannula. The surgical wound was cleaned daily until skin sutures were removed on the 14th postoperative day, when the animals were discharged. During hospitalization, no animal presented pain, edema, subcutaneous emphysema, weight loss, peritonitis or died. One sheep presented moderate necrosis of the ruminal mucosa at the wound edge where the cannula was inserted. Another sheep had a cannula fall out 18 days after the surgical procedure, which was solved by placing the cannula’s internal support in direct contact with the rumen mucosa. Discussion: In small ruminants, most surgical procedures are performed with the patient in a recumbent position. However, rumenostomy in the quadrupedal position was used in this study to allow proper maintenance of the anatomical planes, including fixation of the rumen according to its natural topography. The protocol used for analgesia, sedation and infiltrative local anesthesia was adequate for the surgical procedure, keeping the sheep calm and without signs of discomfort. Manual restraint was effective in maintaining this position throughout surgery and prevented complications associated with right lateral recumbency described in the literature. The surgical technique used provided good positioning of the cannulas and adequate sealing, with no complications related to contamination of the abdominal cavity or surgical wound. Performing the surgery in a single stage reduced the duration of post-operative care when compared to the 2-stage rumenostomy technique described in the literature and also allowed the animals to be promptly included in the digestibility study. Necrosis of the rumen mucosa in contact with the cannula is a common complication due to the cannula’s compression against the tissues, which does not result in significant clinical consequences. The fall of the cannula in 1 sheep can be explained by weight loss, likely due to its inability to adapt to the food provided during the study, after hospital discharge. It can be concluded that the anesthetic and surgical techniques employed in this study for performing rumenostomy in standing sheep were effective and safe. The animals adapted well to the cannula, with no signs of discomfort, pain or altered physiological behavior. Keywords: fistulization, quadrupedal position, rumen, surgery. Título: Rumenostomia e inserção de cânula flexível em ovinos: técnica anestésica e cirúrgica em posição quadrupedal Descritores: fistulização, posição quadrupedal, rúmen, cirurgia.